Isoflavonoid metabolism in leguminous plants: an update and perspectives - Yang, Qilin; Wang, Guodong (Frontiers in Plant Science, 2024)
Isoflavonoids constitute a well-investigated category of phenylpropanoidderived specialized metabolites primarily found in leguminous plants. They play a crucial role in legume development and interactions with the environment.Isoflavonoids usually function as phytoalexins, acting against pathogenic microbes in nature. Additionally, they serve as signaling molecules in rhizobial symbiosis. Notably, owing to their molecular structure resembling human estrogen, they are recognized as phytoestrogens, imparting positive effects on human health. This review comprehensively outlines recent advancements in research pertaining to isoflavonoid biosynthesis, transcriptional regulation, transport, and physiological functions, with a particular emphasis on soybean plants. Additionally, we pose several questions to encourage exploration into novel contributors to isoflavonoid metabolism and their potential roles in plantmicrobe interactions.